2016
DOI: 10.1080/10610278.2015.1136412
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into cluster formation with alkyl-tethered bis-calix[4]arenes

Abstract: Investigations into cluster formation with alkyl-tethered biscalix[4]arenes Abstract: Calix[4]arenes are versatile ligands capable of forming a wide range of cluster motifs when reacted with 3d, 4f or 3d/4f metal ions. Synthetic modification at the calix[4]arene methylene bridge offers a unique opportunity to explore cluster formation with these alternative building blocks. Here we present the synthesis of a range of bis-calix[4]arenes that are tethered by alkyl chains, as well as exploratory structural studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…One of the most challenging structural modifications of the calixarene scaffold is the selective introduction of substituents on the methylene groups of the macrocycle. Fantini and co-workers developed a very useful methodology for the preparation of calix[4]­arene derivatives monosubstituted at a single methylene bridge. The method involves lithiation ( n -BuLi/TMEDA) of a methylene group of the tetramethyl ether of calix[4]­arene ( 1 ) followed by reaction of the metalated calixarene with an alkyl halide (eq ) or, more generally, with an electrophile. Although a large excess of n -BuLi is used in the metalation step, the reaction affords calix[4]­arene derivatives with only a single bridge monosubstituted ( 4 ).…”
mentioning
confidence: 99%
“…One of the most challenging structural modifications of the calixarene scaffold is the selective introduction of substituents on the methylene groups of the macrocycle. Fantini and co-workers developed a very useful methodology for the preparation of calix[4]­arene derivatives monosubstituted at a single methylene bridge. The method involves lithiation ( n -BuLi/TMEDA) of a methylene group of the tetramethyl ether of calix[4]­arene ( 1 ) followed by reaction of the metalated calixarene with an alkyl halide (eq ) or, more generally, with an electrophile. Although a large excess of n -BuLi is used in the metalation step, the reaction affords calix[4]­arene derivatives with only a single bridge monosubstituted ( 4 ).…”
mentioning
confidence: 99%
“…In this case one of the equatorial ions from the octahedron has been omitted due to the targeted 'expansion' of the lower-rim binding pocket; this Ln III ion omission coincides directly with the position of the ethereal bridge. We also recently tethered C [4]s with alkyl chains of varying length through synthetic modification at one methylene bridge position (25). In doing so we found cluster formation with these bis-C [4]s to be challenging, except in cases where the tether was long enough to allow the constituent C [4]s to form previously reported cluster topologies (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The C [4] showing that this is a versatile cluster topology for C [4]. Reactions containing both 3d and 4f ions give several different heterometallic clusters depending on the stoichiometries and metal salts employed (6,8,10,24), an interesting example of which is the ability to systematically interchange the body ions in the In addition to carrying out such exploratory work with C [4], we have also reported on aspects of binding site alteration and the subsequent effect this has on cluster formation / composition (25)(26)(27). Our first effort in this regard was to employ oxacalixarenes to systematically vary the size of the tetraphenolato pocket (26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…21 Indeed, we have recently shown that it is possible to tether H 4 TBC [4]s with a range of other linkers of varying degrees of flexibility/ rigidity. 22,23 The mobility of H 8 L1 gives rise to many conformational possibilities. However, if one of the H 4 TBC [4] moieties in Fig.…”
Section: Introductionmentioning
confidence: 99%